Genome-wide identification and analysis of glyceraldehyde-3-phosphate dehydrogenase family reveals the role of GmGAPDH14 to improve salt tolerance in soybean (Glycine max L.) - Zhao, Xunchao; Wang, Jie; Xia, Ning; Qu, Yuewen; Zhan, Yuhang; Teng, Weili; Li, Haiyan; Li, Wenbin; Li, Yongguang; Zhao, Xue; Han, Yingpeng (Frontiers in Plant Science, 2023)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is an essential key enzyme in glycolytic metabolic pathway, and plays an important role in stress responses. Although GAPDH family genes have been found in different plant species, their determination of gene family analysis and functional roles in soybean are still unknown. In this study, gene sequence and expression data were obtained using online tools, and systematic evolution, expression profile and qRT-PCR analysis were conducted. Here, a total of sixteen GmGAPDH genes were identified on nine chromosomes, which were classified into three clusters. Additionally, all GmGAPDH genes harbor two highly conserved domains, including Gp_dh_N (PF00044) and Gp_dh_C (PF02800). The qRT-PCR analysis also showed that most GmGAPDH genes were significantly responded to multiple abiotic stresses, including NaHCO3, PEG, Cold, and Salt. Of them, GmGAPDH14, was extraordinarily induced to salt stress. The GmGAPDH14 gene was cloned and overexpressed through soybean hair roots. The overexpressed transgenic soybean plants of GmGAPDH14 gene also were shown better growth than that of control plants. Moreover, the overexpressed transgenic plants of GmGAPDH14 gene had higher activities of superoxide dismutase (SOD), but lower malonaldehyde (MDA) content than that of control plants under salt stress. Meantime, a total of four haplotypes were found for GmGAPDH14 gene and haplotype 2, 3 and 4 were beneficial for tolerance of soybean to the salt stress. These results suggest that the GmGAPDH14 gene might be involved in the process of soybean tolerance to salt stress. These results of this study will be valuable to understand the role of GAPDH genes in abiotic stress response of soybean.